2015
DOI: 10.1021/acs.estlett.5b00159
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal Concentrations of Silver Nanoparticles Stimulate Biofilm Development

Abstract: Although silver nanoparticles (AgNPs) are used as antimicrobial agents in a wide variety of commercial products, sublethal exposure can counterproductively promote the development of biofilms. We observed by fluorescence microscopy denser biofilm growth with mixed cultures from a wastewater treatment plant after exposure to 21.6 μg/L 10 nm AgNPs. To further understand biofilm promotion mechanisms, experiments were conducted with a pure culture of Pseudomonas aeruginosa PAO1. Sublethal exposure of PAO1 to AgNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 66 publications
3
48
0
Order By: Relevance
“…This suggests that P. fluorescens bacteria respond to the silver stress by forming biofilms, even though in the current situation the source of the stress is the silver ion released from the AgNPs that are adsorbed on the substrate. This supports the recent report that exposure to sublethal concentrations of suspended AgNPs stimulates biofilm development [49]. Since this high biofilm coverage is observed on both the uncoated and coated regions of the same coverslip, it must result from dissolved silver effects.…”
Section: This Is Corroborated Bysupporting
confidence: 90%
See 1 more Smart Citation
“…This suggests that P. fluorescens bacteria respond to the silver stress by forming biofilms, even though in the current situation the source of the stress is the silver ion released from the AgNPs that are adsorbed on the substrate. This supports the recent report that exposure to sublethal concentrations of suspended AgNPs stimulates biofilm development [49]. Since this high biofilm coverage is observed on both the uncoated and coated regions of the same coverslip, it must result from dissolved silver effects.…”
Section: This Is Corroborated Bysupporting
confidence: 90%
“…The inoculum concentration controls the silver to biomass ratio in the system. The importance of this ratio is also indicated by recent evidence that exposure to sublethal concentrations of suspended AgNPs stimulates biofilm formation, perhaps as an environmental stress response [49]. The effect of inoculum concentration on the anti-colonization performance of silver-laden surfaces must be considered explicitly, both for antifouling surface engineering and for understanding the environmental implications of AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] By contrast, 1 lg/ml AgNPs promoted adhesion in B. subtilis under aerobic conditions, the same condition that increased the MSGR in the planktonic growth tests. Recently, Yang and Alvarez 15 reported that sublethal exposure of Pseudomonas aeruginosa PAO1 to AgNP enhanced biofilm development and upregulated quorum sensing, lipopolysaccharide biosynthesis, and antibiotic resistance (efflux pump) genes.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Indeed, predicted environmental concentrations of AgNPs ranging from 1 pg/ml to 10 lg/ml have been found in both solid and liquid environmental matrixes. 14,[57][58][59] To the best of our knowledge, only a few scientific works have investigated the effects of sublethal AgNP concentrations on microbial systems; [15][16][17] therefore, their impact on microbial physiology and behavior still remains almost unknown. Moreover, despite the growing body of literature regarding nanoparticles in biosolids, [51][52][53] little is known about the effects of sublethal concentrations of AgNPs on anaerobic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the silver nanoparticles (AgNPs) showed promising antimicrobial activity on various microbial strains [80]. Recently, Yang et al [81] discovered that the sublethal concentrations of AgNPs promoted the formation of biofilms by P. aeruginosa via upregulating a complex genetic networks associated with QS, EPS, as well as the antibiotic resistance genes. Upadhyayulaa and Gadhamshettyb [82] reported that the carbon nanotubes and their composites possess the capability of inducing biofilm formation as well at low level concentrations as well, while they were traditionally regarded as antimicrobial materials.…”
Section: The Inducing Effects Of Sublethal Levels Of Stressors On Biomentioning
confidence: 99%